Use of magnetic fields and nanoparticles to trigger drug release and improve tumor targeting. (26th June 2019) - Liu, Jessica F.; Jang, Bian; Issadore, David; Tsourkas, Andrew
Abstract: Drug delivery strategies aim to maximize a drug's therapeutic index by increasing the concentration of drug at target sites while minimizing delivery to off‐target tissues. Because biological tissues are minimally responsive to magnetic fields, there has been a great deal of interest in using magnetic nanoparticles in combination with applied magnetic fields to selectively control the accumulation and release of drug in target tissues while minimizing the impact on surrounding tissue. In particular, spatially variant magnetic fields have been used to encourage accumulation of drug‐loaded magnetic nanoparticles at target sites, while time‐variant magnetic fields have been used to induce drug release from thermally sensitive nanocarriers. In this review, we discuss nanoparticle formulations and approaches that have been developed for magnetic targeting and/or magnetically induced drug release, as well as ongoing challenges in using magnetism for therapeutic applications. This article is categorized under: Diagnostic Tools > in vivo Nanodiagnostics and Imaging Therapeutic Approaches and Drug Discovery > Emerging Technologies Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Magnetic fields can be used in combination with magnetic nanoparticles to trigger drug release from thermally sensitive nanocarriers or increase drug accumulation at a target site via magnetic drug targeting.